THE ROLE OF SURGEONS DURING THE COVID-19 PANDEMIC - THE EXPERIENCE OF THE SURGERY CLINIC OF THE CLINICAL HOSPITAL CENTER ZEMUN: The experience of the Surgery Clinic of Clinical Hospital Center "Zemun" - Stojanović, Dragoš; Mitrović, Nebojša; Stevanović, Dejan; Jašarović, Damir; Milina, Srđan; Surla, Dimitrije; Radmilović, Slobodan; Ilić, Goran; Lazić, Aleksandar; Lukić, Branko; Radišić, Dejan (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: In December of 2019, the existence of a new type of disease, caused by SARS coronavirus 2 (SARS-CoV-2), was discovered in Wuhan, Republic of China. The disease itself is characterized by a large number of patients with moderate and severe clinical presentation, who required hospital treatment. The organization of the health system of our country during the aforementioned pandemic, required the engagement of all doctors, regardless of their specialty, in the treatment of patients with covid. Surgeons of all branches, from the Surgery Clinic of the Clinical Hospital Centre Zemun, were directly engaged in the treatment of both primary manifestations of the virus and numerous surgical complications arising in the wake of this disease, but also primary acute surgical diseases in COVID-positive patients. Aim: The aim of this paper is to present the work of the Surgery Clinic of CHC Zemun in the conditions of the COVID pandemic, as well as to present the types and results of surgeries performed in patients with COVID infection. Methods: This study was conceived as a retrospective study and was conducted in the period from February 2020 to April 2021 in patients who underwent emergency surgery and in whom COVID infection was previously verified. A total of 232 patients who were surgically treated at the level of the entire Surgery Clinic of the CHC Zemun participated in the study. Results: Chest drainage due to development of pneumothorax accounted for a quarter of all interventions, while surgical treatment was undertaken in 53.85% of cases due to acute abdomen of various etiologies, or vascular diseases in 21.15% of cases. Conclusion: The COVID pandemic is in itself a major challenge for the entire healthcare. The role of surgeons is significant, both in organization and in direct treatment, which is additionally complicated by the uniqueness of the entire situation and the severity of the disease itself. In addition to partaking in the treatment of COVID infection itself, surgeons were engaged in a large number of cases in their primary activity in health care, that is, in the treatment of surgical diseases and complications of COVID, performing demanding surgical procedures in very difficult and unique conditions.